2014
DOI: 10.1186/1471-2199-15-17
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the physical and functional interaction between hMYH and hRad9 by Dronpa bimolecular fluorescence complementation

Abstract: BackgroundHuman MutY glycosylase homolog (hMYH), a component of the base excision repair pathway, is responsible for the generation of apurinic/apyrimidinic sites. Rad9-Rad1-Hus1 (9-1-1) is a heterotrimeric protein complex that plays a role in cell cycle checkpoint control and DNA repair. In humans, hMYH and 9-1-1 interact through Hus1 and to a lesser degree with Rad1 in the presence of DNA damage. In Saccharomyces pombe, each component of the 9-1-1 complex interacts directly with SpMYH. The glycosylase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, Agustina et al . [45] showed that hRad9 interacts with N-terminal region (residues 1–74) of hMYH. Thus, the physical interactions of MYH with Hus1 and Rad9 appear different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Agustina et al . [45] showed that hRad9 interacts with N-terminal region (residues 1–74) of hMYH. Thus, the physical interactions of MYH with Hus1 and Rad9 appear different.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that deletion of fission yeast S. pombe SpMyh1 strongly abrogated the association of SpHus1 with telomeres [51]. hMYH knockdown in human cells decreases Chk1 and Cdc25C phosphorylation in response to H 2 O 2 treatment [52] and decreases p-Chk1 and p-Cdk2 after hydroxyurea treatment [45]. Thus, we suggest that MYH first recognizes a mismatch then recruits 9-1-1 to sites of DNA damage through MYH-Hus1 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…HU is an inhibitor of ribonucleotide reductase that inhibits DNA replication in cells [ 18 , 21 , 22 ]. HU induces the accumulation of ROS and cell death.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found that depletion of hMYH disrupts ATR and Chk1 activation following hydroxyurea (HU) and ultraviolet treatment [ 17 ]. In addition, we also observed endogenous interactions between hTopBP1 and hMYH as well as hRad9 and hMYH [ 5 , 18 ]. These observations support the claim that hMYH is an important component of the ATR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%